Front Cover: SAR Studies of the Leupyrrins: Design and Total Synthesis of Highly Potent Simplified Leupylogs (Chem. Eur. J. 66/2020). Issue 66 (15th October 2020) - Wosniok, Paul R.; Knopf, Christopher; Dreisigacker, Sandra; Orozco‐Rodriguez, J. Manuel; Hinkelmann, Bettina; Mueller, Peter P.; Brönstrup, Mark; Menche, Dirk
Abstract : The design and total synthesis of dramatically simplified leupylogs is presented. They demonstrate similar highly potent antifungal activities as the natural leupyrrins, as depicted by a balanced IC50 weighing scale. The origin of the secondary metabolites from the myxobacterium Sorangium cellulosum is illustrated by its fruiting bodies while the flask portrays the synthetic endeavors which have led to the discovery of leupylogs. More information can be found in the Communication by D. Menche et al. on page 15074 .